Tax Evasion and Tax Avoidance: Effects on the Internal Revenue - Kaur, Gurpreet; Aanchal (Gyan Management Journal, 2019)
Tax is that part of an individual’s total income which helps the government to increase their revenue. This amount is being utilized by the government for the purpose of development of the country such as for the purpose of construction of buildings, roads etc. But, it has been found that the country has to face various problems through tax evasion and avoidance. The aim of the study is to identify the reasons and effects of tax evasion and tax avoidance. This study has used the secondary data from the annual reports, from magazines etc. The findings of the study showed the amount of actual revenue collected by the government have had a huge difference than the revenue expected by the government. The reason behind this is tax evasion and avoidance. It has been conclude in this study that that these two affects the internal economy badly. The revenue of government gets decreased due to which government is not able to take positive measures for the benefits of the country. It has been recommended that if the amount of taxes will decrease, the problem can be reduced to a great extent.